Thermotolerance of tax-2 Is Uncoupled From Life Span Extension and Influenced by Temperature During Development in C. elegans - Hwang, Ho-Yon; Dankovich, Laura; Wang, Jiou (Frontiers in Genetics, 2020)
Thermotolerance of an organism is a complex trait that is influenced by a multitude of genetic and environmental factors. Many factors controlling thermotolerance in Caenorhabditis elegans are known to extend life. To understand the regulation of thermotolerance, we performed a genetic screen for mutants with better survival at warm temperature. Here we identified by dauer survival a tax-2 mutation and several mutations disrupting an insulin signaling pathway including the daf-2 gene. While the tax-2 mutant has improved thermotolerance and long life span, the newly identified daf-2 and other insulin signaling mutants, unlike the canonical daf-2(e1370), do not show improved thermotolerance despite being long-lived. Examination of tax-2 mutations and their mutant phenotypes suggest that the control of thermotolerance is not coupled with the control of life span or dauer survival. With genetic interaction studies, we concluded that tax-2 has complex roles in life span and dauer survival and that tax-2 is a negative regulator of thermotolerance independent of other known thermotolerance genes including those in the insulin signaling pathway. Moreover, cold growth temperature during development weakens the improved thermotolerance associated with tax-2 and other thermotolerance-inducing mutations. Together, this study reveals previously unknown genetic and environmental factors controlling thermotolerance and their complex relationship with life span regulation.